Cloud computing advancements in design, implementation, and technologies - Aljawarneh, Shadli (Information Science Reference, 2013)
"This book outlines advancements in the state-of-the-art standards and practices of cloud computing, in an effort to identify emerging trends that will ultimately define the future of the cloud"--Provided by publisher